Exploring Improvement Paths for Eight Industrial Symbiosis Complexes throughout the World - Zheng, Hongmei; Zhang, Yan; Yang, Zhifeng; Liu, Gengyuan; Su, Meirong; Chen, Bin; Meng, Xiaojie; Li, and Yating (Journal of Environmental Accounting and Management, 2026)
Industrial symbiosis complexes have been developing throughout the world for nearly seventy years since 1947, “industrial symbiosis” was proposed firstly. Unfortunately, due to the changes of the exchanges between members or the disappearance or newly-built activities of some members, only a few complexes developed smoothly and sustainably, such as Kalundborg industrial symbiosis complex. Therefore, it is necessary to plan and redesign exist-ing industrial symbiosis complexes. In this study, we firstly combined with density and network degree centralization metrics in network analysis method and divided these complexes into three different types: dependence-oriented (Guangxi, Xinjiang, and Ka-lundborg), equality-oriented (Choctaw and Lubei), and nested-oriented complexes (Kitakyushu, Tianjin, and Styria), then summarized their similarities. Secondly, we can propose new established exchanges for all the eight industrial symbiosis complexes throughout the world from the perspective of analyzing their deficiencies in structural characteristics and calculate how the effectiveness of these new linkages. This study can provide basis for the resource utilization efficiencies improvement and the stable and sustainable development of these complexes.